THE PROPORTION AND DYNAMICS OF MOSQOITO LARVAE OF AEDES, ANOPHELES, AND CULEX IN DENPASAR - Aryani, Nina; Pasti Apsari, Ida Ayu; Haryono Utama, Iwan (Jurnal Veteriner, 2008)
This research was aimed to observe the proportion and the dynamics of mosquito larvae of Aedes, Anopheles, and Culex in Denpasar-Bali. Larva samples were collected from several areas such as Sanggaran’s abattoir, rice fields, water drainages and water container in densely-populated area. Sample collections were conducted three times in two week interval. Larvae was identified macroscopically and microscopically and three species of larvae, Aedes, Anopheles, Culex were subjected for further study. The distribution and composition of larvae at rice field (Anopheles and Culex) and pond (Aedes and Culex) were not significantly different (P>0,05) within the first (mid of July 2003), second (early August 2003), and the third (mid August 2003) periods of observation. At the third period, however, Culex larvae was observed besides of Aedes larvae. The composition of mosquito larvae was relatively unchanged during three periods of sampling, except the occurrence of Culex larvae in pond in third period of sampling.
Keywords: Aedes, Anopheles, Culex larvae, proportion, distribution, dynamics